The bactericidal efficiency of Chlorhexidine as an endodontic irrigant - Abdul-Haq A Suliman; Ghada Y. Abdul- Rahman; Wiam M. Al-Ashou (University of Mosul, College of Dentistry, 2006)
Aims: to determine the bactericidal efficiency of 0.75% Chlorhexidine in vitro . The time required for this irrigant to start its antimicrobial effect on the selected microorganisms isolated from the infected root canals and unidentified samples taken from root canals with necrotic pulps were evaluated. Materials and Methods: The substantive antimicrobial effect of 0.75% Chlorhexidine in vitro is also considered. Samples taken from 13 teeth with necrotic pulp from patients attended the Department of Conservative Dentistry, College of Dentistry at Mosul University. The turbidity method was applied to determine the antimicrobial effect of 0.75% Chlorhexidine and the combination of 0.5% Chlorhexidine and 0.5% sodium hypochlorite comparing with the antimicrobial effect of 2.5% sodium hypochlorite, the time required for these materials to start their antimicrobial effect on the selected microorganisms was determined using contact test. The antimicrobial effectiveness were evaluated at different time intervals, immediately, 5, 10, 15 minutes after the contact of the microorganisms with the irrigating solutions. Results: Both 0.75% Chlorhexidine and 2.5% sodium hypochlorite are effective on microorganisms collected from root canal. There is no significant difference between Chlorhexidine and sodium hypochlorite in their antimicrobial effect on the anaerobic microorganisms, but Chlorhexidine is more effective on the aerobic microorganisms. Conclusion: Chlorhexidine 0.75% and 2.5% sodium hypochlorite has an immediate effect on the selected microorganisms and unidentified samples from the teeth with necrotic pulps. The combination of Chlorhexidine 0.5% and 0.5% sodium hypochlorite has an effect started after 5 minutes